57x+4334635x-30409234809x=28934237409x+23423423x*12312321x

Simple and best practice solution for 57x+4334635x-30409234809x=28934237409x+23423423x*12312321x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of you

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 57x+4334635x-30409234809x=28934237409x+23423423x*12312321x equation:


Simplifying
57x + 4334635x + -30409234809x = 28934237409x + 23423423x * 12312321x

Combine like terms: 57x + 4334635x = 4334692x
4334692x + -30409234809x = 28934237409x + 23423423x * 12312321x

Combine like terms: 4334692x + -30409234809x = -30404900117x
-30404900117x = 28934237409x + 23423423x * 12312321x

Reorder the terms for easier multiplication:
-30404900117x = 28934237409x + 23423423 * 12312321x * x

Multiply 23423423 * 12312321
-30404900117x = 28934237409x + 288396702900000x * x

Multiply x * x
-30404900117x = 28934237409x + 288396702900000x2

Solving
-30404900117x = 28934237409x + 288396702900000x2

Solving for variable 'x'.

Combine like terms: -30404900117x + -28934237409x = -59339137526x
-59339137526x + -288396702900000x2 = 28934237409x + 288396702900000x2 + -28934237409x + -288396702900000x2

Reorder the terms:
-59339137526x + -288396702900000x2 = 28934237409x + -28934237409x + 288396702900000x2 + -288396702900000x2

Combine like terms: 28934237409x + -28934237409x = 0
-59339137526x + -288396702900000x2 = 0 + 288396702900000x2 + -288396702900000x2
-59339137526x + -288396702900000x2 = 288396702900000x2 + -288396702900000x2

Combine like terms: 288396702900000x2 + -288396702900000x2 = 0
-59339137526x + -288396702900000x2 = 0

Factor out the Greatest Common Factor (GCF), '-2x'.
-2x(29669568760 + 144198351500000x) = 0

Ignore the factor -2.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(29669568760 + 144198351500000x)' equal to zero and attempt to solve: Simplifying 29669568760 + 144198351500000x = 0 Solving 29669568760 + 144198351500000x = 0 Move all terms containing x to the left, all other terms to the right. Add '-29669568760' to each side of the equation. 29669568760 + -29669568760 + 144198351500000x = 0 + -29669568760 Combine like terms: 29669568760 + -29669568760 = 0 0 + 144198351500000x = 0 + -29669568760 144198351500000x = 0 + -29669568760 Combine like terms: 0 + -29669568760 = -29669568760 144198351500000x = -29669568760 Divide each side by '144198351500000'. x = -0.0002057552562 Simplifying x = -0.0002057552562

Solution

x = {0, -0.0002057552562}

See similar equations:

| 7t-8=2+5t | | -2+p+2p+2=-12 | | 5m-12=-10+4m | | -36-b-4b=64 | | 5m+1=-23 | | 11.3-7.2=-3.82 | | 1.3-7.2=-3.82 | | 8.4s-s=14.8 | | -5z+3z-7=8z-1-6 | | 3x-2=4x-8 | | 7n^2-43n+6=0 | | n^2=n | | 7p^2-27p-40=0 | | 5a=20 | | -7=2y-3-3y | | 3x-7(-2x+8)=-5 | | 3x-7y=-5 | | 10n+8p=0 | | S=3t+40 | | (x-1)+(x+3)=2x | | k-8(7+k)=-1(5) | | 4t-3-3t=-5 | | 9x+3y=4 | | (3x+4)(2-5x)=0 | | c=(2)(3.14)(r) | | 9x-4y=-2 | | 6.3y=4.1y+12 | | 1.2=1.6m | | c=23 | | -8=5a-3a | | -54=133.578499968x+0.5*0.0209625668*17843.21565 | | 6(x+2)-(3x-8)= |

Equations solver categories